Conversion of d-xylose into furfural with aluminum and hafnium pillared clays as catalyst (2013)
The industrial practice used to produce furfural is the dehydration of pentoses, which is carried out using highly corrosive and contaminating mineral acid catalysts. Because of the ecological and toxicological threats of this process and the complexity of product separation associated with these substances, the development of new acid solid catalysts has expanded in recent years. The present work is focused on the production of furfural from D-xylose using aluminum and hafnium pillared clays as catalysts. After 4 h of reaction at temperatures ranging between 140 and 170°C, conversion rates of 50-80% were observed, and selectivity levels of 40-65% were reached. Finally, the stability of the catalyst was further investigated by applying a thermal treatment prior to reuse. A significant decrease in the selectivity was not observed in four consecutive reactions. Consequently the pillared clays appear to be active, selective and stable catalyst for pentose dehydration.